The information and communication technology (ICT) as a marketing tool at the Telekom Training College Sarawak / Patricia Robert Tasser - Robert Tasser, Patricia (2003)
The modern and developing life in the new century has brought to the rapprochement of sciences and technology nowadays. People more sophisticated and high demand through the latest and high-tech equipment in order to make their life full of satisfaction. In actual, this phenomenon has drastically influence business today. This is why the new approach of sciences and technology promising high return of income and profit and high quality of product, services and valuable information’s. ICT or known as Information and Communication technology is an example of updated technology equipment widely use in business. Telekom Training College is the companies that practicing this types of technology to achieve their mission and target through ISO 9000. TTC is dealing on education and training in Kuching area. Besides that, they also do marketing job especially in promoting their facilities in Telekom Training College Jalan Semariang. In fact, Information and Communication Technology (ICT) can find most in software programs that cater much information, which may help to generate any types of information valuable to the company itself. The company must consider any incoming implication to ensure that they have chosen Information and Communication Technology (ICT) appliances as the correct choice and consequently not defeat all mission.